Performance Analysis of Nyamplung Oil (Calophyllum Inophyl-lum) as an Alternative Liquid Electrical Insulation Material to Replace For Power Transformer Oil - Lukman Lukman; Yanuar Zulardiansyah Arief; Adhes Gamayel; Sinka Wilyanti (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
In the operation of electric power distribution, the transformer can be said to be the heart of the transmission and distribution of electric power. In recent years the use of vegetable oil is increasing. The purpose of this study was to test and analyze a mixture of transformer oil and nyamplung oil (Calophyllum Inophyllum) as transformer insulation and also to obtain the best composition of nyamplung oil which can be used as an alternative to transformer oil. This research method tested the parameters of nyamplung oil and a mixture of nyamplung oil and mineral oil (Shell Diala S4), such as; viscosity, flash point, density, pour point, acidity, moisture content and breakdown voltage. The sample test results are then compared with standard mineral oil according to IEC 60296-2003. From the analysis conducted, it was found that TRNY10 oil mixture (10% transformer oil and 90% mineral oil) has the best potential as power transformer oil.